Corrosion protection by sacrificial anode method on underground solar pipe installation: a case study in the Lombok Gas Engine Combine Cycle Power plant (Peaker) 130-150 MW - Nasmi Herlina Sari; Suteja; R.C. Lelio (University of Muhammadiyah Malang, 2021)
This study aims to determine cathodic and design corrosion protection by sacrifice anode method in underground solar pipe installations. The material used is a steel pipe. The length of pipes in the ground 35,384 m and a diameter of 150 mm. The type of anode used is high magnesium. The result shows that the large area that must be protected 16.67 m2. The pipe protection current requirement is 0.81 A. The total number of anodes is 208.69 kg. Anode installation distance 2.36 m. Requirement of protection current based on the distance between the anode is 12.06 A. To protect the pipe along 35,384 m, the ideal amount of magnesium anode used is 208.69 kg. The results of the verification of the cathodic protection system design of the anode victim of the lower solar pipe show that the total number of anodes to supply a current of 0.81 A in order to protect the pipe is 15 pcs.